Optimization of Gelatin and Pectin Combination as a Gelling Agent in the Formulation of Flawless Jelly Preparations with Ethanol Extracts of Meniran (Phyllanthus Niruri) and Kelor (Moringa Oleifera) - Sari, Tiara Nastiti; Suprapto (International Journal of Medical Science and Clinical Research Studies, 2025)
Formulating the Jelly Flawless preparation using extracts of meniran (Phyllanthus niruri) and Moringa (Moringa oleifera) which are rich in antioxidants. Antioxidants have an important role in the body by protecting cells from damage caused by free radicals. The Jelly Flawless formulation with ethanolic extracts of meniran (Phyllanthus niruri) and kelor (Moringa oleifera), combined with gelatin and pectin, affects the hardness test, showing no significant hardness in the fourth formulation. It contains positive secondary metabolites such as tannins, alkaloids, saponins, flavonoids, quinones, and steroids. The antioxidant test results for the extracts of meniran (Phyllanthus niruri) and kelor (Moringa oleifera) were 5.55 µg/mL, higher than the positive control of vitamin C of 2.78 µg/mL, indicating that the ethanolic extracts of Phyllanthus niruri and Moringa oleifera contain strong antioxidants. Therefore, the Jelly Flawless formulation of ethanolic extracts of meniran (Phyllanthus niruri) and kelor (Moringa oleifera) can be produced and consumed because it contains strong antioxidants that have an important role in the body.